Futile treatment: Medical and Theological approach - Volteas, Spiridon K; Fanaras, Vasileios (Bioethica, 2021)
This is a medical and theological approach of Futile Treatment, an issue that raises severe medical and bioethical dilemmas. We discuss the difficulties in establishing objective criteria to discontinue treatment and present the theological views on the subject with emphasis to orthodox theology. This paper aims to contribute to the subject and also rise a debate in Greece.